ความสัมพันธ์ระหว่างการบริหารตามหลักธรรมาภิบาลกับประสิทธิผลของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษายะลา เขต 3 - ซียง อัลอามีน; ศิริสุข กนกกร (Al-HIKMAH Journal, 2021)
This independent study aimed to 1) study good governance administration of school administrators under Yala Primary Educational Service Area, Office 3, 2) study school effectiveness under Yala Primary Educational Service Area, Office 3, and 3) study the relationship of good governance administration and school effectiveness under Yala Primary Educational Service Area, Office 3. The subject consisted of 193 teachers in school under Yala Primary Educational Area, Office 3 in the A.D. 2021 academic year, using Krejcie and Morgan’s table in setting sample size, the stratified random sampling technique in classifying school size and the simple random sampling technique in choosing the subject. Research tools were five-scale questionnaires. Statistics used in this research included percentage, mean, standard deviation and Pearson’s Product Moment Correlation Coefficient. The findings of the study reveal the following 1) Good governance administration of school administrators under Yala Primary Educational Service Area, Office 3 was at the high level, both overall picture and each aspect. The aspect that received the highest mean score was participation principle, followed by ethics principle, responsibility principle, value for money principle, transparency principle and rule of law consecutively. 2) The school effectiveness under Yala Primary Educational Service Area, Office 3 was at the high level, both overall picture and each aspect. The aspect that received the highest mean score was the effectiveness on internal problem solving, followed by the effectiveness on the change and development in the school, enhancement of positive attitude in students, and producing high-achievement students consecutively. 3) The relationship between good governance administrators and school effectiveness under Yala Primary Educational Service Area, Office 3 was significantly and highly positive (r=.733) at the .01 level.